Planificación del mantenimiento preventivo para los neumáticos de la flota de tractocamiones para optimizar su disponibilidad de la empresa grupo transpesa sac - Ruiz Rodríguez, Percy Ivan (2018)
In the present paper of investigation, the planning of the preventive maintenance for the tires of the fleet of Tractor trucks was carried out of the company Grupo Transpesa S.A. to increase its availability as a logistics operator. With the objective of implementing the planning of preventive maintenance by applying tire inspection information, which allows us to analyze the status of the tire for the correct application of methodologies to achieve the maximum cost benefit, extending the useful life, knowing the properties, applications and operation of the tires. The procedure followed for the development of this paper is defined by the following stages: Identification of fleet operation regime, adequate tire selection, implementation of control kpis (indicators) and maintenance programming. As a result of the study, the fleet availability increased from 85% to 93%, as well as tire selection formats, control and fleet management formats, management indicators and maintenance record. Finally, it is concluded by analyzing and identifying the main causes why a tire can become a scrap and establishing recommendations to ensure correct use, extending its useful life.